Smart Intelligent Aircraft Structures (SARISTU) Proceedings of the Final Project Conference - Wölcken, Piet Christof; Papadopoulos, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The book includes the research papers presented in the final conference of the EU funded SARISTU (Smart Intelligent Aircraft Structures) project, held at Moscow, Russia between 19-21 of May 2015. The SARISTU project, which was launched in September 2011, developed and tested a variety of individual applications as well as their combinations. With a strong focus on actual physical integration and subsequent material and structural testing, SARISTU has been responsible for important progress on the route to industrialization of structure integrated functionalities such as Conformal Morphing, Structural Health Monitoring and Nanocomposites. The gap- and edge-free deformation of aerodynamic surfaces known as conformal morphing has gained previously unrealized capabilities such as inherent de-icing, erosion protection and lightning strike protection, while at the same time the technological risk has been greatly reduced. Individual structural health monitoring techniques can now be applied at the part-manufacturing level rather than via extending an aircraft's time in the final assembly line. And nanocomposites no longer lose their improved properties when trying to upscale from neat resin testing to full laminate testing at element level. As such, this book familiarizes the reader with the most significant develo pments, achievements and key technological steps which have been made possible through the four-year long cooperation of 64 leading entities from 16 different countries with the financial support of the European Commission.
SARISTU: Six years of project management -- Morphing Wing integrated safety approach and results -- Development and validation of a Bird Strike Protection System for an Enhanced Adaptive Droop Nose -- Adaptive Trailing Edge: Specifications, Aerodynamics and Exploitation -- Structural Design of an Adaptive Wing Trailing Edge for Large Aeroplanes -- Design, Optimization, Testing, Verification, and Validation of the Wingtip Active Trailing Edge -- Winglet design, manufacturing and testing -- Ribbon tapes, shape sensors and hardware -- Methodologies for the Damage Detection based on Fiber Optic sensors. Applications to the fuselage panel and lower wing panel -- Methodologies for guided waves based SHM system implementation on composite wing panels: results and perspectives from SARISTU Scenario 5 -- An electro-mechanical impedance based mobile system for structural health monitoring and reliability check of bonded piezoelectric sensors -- Damage Identification in Composite Panels - Methodologies and Visualisation -- Manufacturing of CFRP panels with integrated sensor network and contacting of the network -- Flat and curved panel manufacturing -- Compression after multiple impacts: modelling and experimental validation on composite coupon specimens -- Piezochromic compounds able to be used in shock detecting paints -- Brittle coating layers for impact detection in CFRP -- Use of Carbon Nanotubes in Structural Composites -- Enhancement of primary structure robustness by improved damage tolerance -- Improvement of the electrical isotropy of composite structures- Overview -- Fabrication of carbon nanotubes doped veils -- Morphing value assessment on overall aircraft level -- Implementation of Morphing, Structural Health Monitoring and  Nanomaterials on an Outer Wing Box -- Fuselage Demonstrators: An overview of the development approach -- Development of a Door Surround Structure with Integrated Structural Health Monitoring System.
Keywords: Aerospace engineering; Astronautics; Materials; Nanotechnology; Aerospace Technology and Astronautics; Materials Engineering; Nanotechnology